(untitled) (Global Journal of Management and Business Research, 2026)
The environment in which Albanian business activities are carried out has changed continuously, as a result of changing economic, political, socio-cultural and technological factors. Businesses, which have become increasingly globalized and interdependent, have begun to carry out all organizational activities in a virtual environment. Businesses are constantly reviewing their managerial practices, to adapt to the constantly increasing complexity of the business landscape in order to benefit from the unique competitive advantage, knowledge. Even the Albanian government itself considers information and communication technology as one of the highest priorities to achieve high living standards and economic growth. Based on the characteristics of Albanian business and considering the fact that firms must struggle for a confrontation between environmental conditions and organizational structures and even more so when environmental conditions impose conflicting requirements on the desired organizational structure, we offer suggestions to make our business as competitive as possible, by getting involved in virtual organizations.